Культурология: учебное пособие / под. ред. Г. В. Драча - Драч Г. В. (Высшее образование, 2008)
Экземпляры: ф. 4 (20090511) / Инвентарный номер: 93231 / Цена: 196.24 / Авт.знак: К 90 / ГРНТИ: 13 / ББК: 71я73